An Interactive Solution for Lateral-Torsional Buckling of the Mono-Symmetric Beam-Columns with Discrete Lateral Bracings. (June 2018) - Mohammadi, Elham; Hosseini, Sayed Sina; AsgariMarnani, Jafar
Abstract: The beam-column members are widely used in civil structures. These members are subjected simultaneously to the axial load and the bending moment. In this paper, the buckling strength and the bracing stiffness requirement of the mono-symmetric beam-columns with discrete lateral bracing have been investigated. For this purpose, a numerical method based on the finite element analysis is developed to calculate the buckling load-set of the mono-symmetric beam-columns. This proposed method is capable to consider the initial geometric imperfection. The proposed method is compared with the results of experimental and numerical studies obtained by previous researchers and the spatial finite element analysis, which it shows good agreement. Also, by using the matrix form of the energy equation, a closed form solution of the bracing stiffness requirement is suggested for an arbitrary number of bracing points. The P-M interaction curve and formula are presented for mono-symmetric beam-columns. The results show that the peak point of the curve occurs at the P = Pey and M = Pey y0, where Pey is Euler's buckling load. Finally, a parametric study is done to investigate the effects of the eccentricity and degree of mono-symmetry on the buckling strength and bracing stiffness requirement.